Facile Synthesis of B/P Co-Doping Multicolor Emissive Carbon Dots Derived from Phenylenediamine Isomers and Their Application in Anticounterfeiting - Li, Zhiwei (Nanomaterials (Basel, Switzerland), 2024)
Carbon dots (CDs) possess a considerable number of beneficial features for latent applications in biotargeted drugs, electronic transistors, and encrypted information. The synthesis of fluorescent carbon dots has become a trend in contemporary research, especially in the field of controllable multicolor fluorescent carbon dots. In this study, an elementary one-step hydrothermal method was employed to synthesize the multicolor fluorescent carbon dots by co-doping unique phenylenediamine isomers (o-PD, m-PD, and p-PD) with B and P elements, which under 365 nm UV light exhibited signs of lavender-color, grass-color, and tangerine-color fluorescence, respectively. Further investigations reveal the distinctness in the polymerization, surface-specific functional groups, and graphite N content of the multicolor CDs, which may be the chief factor regarding the different optical behaviors of the multicolor CDs. This new work offers a route for the exploration of multicolor CDs using B/P co-doping and suggests great potential in the field of optical materials, important information encryption, and commercial anticounterfeiting labels.